The Influence Of Profitability, Leverage, And Company Size On Tax Avoidance Practices In Public Companies - Ilham Teruna Bakti; Yudi Budi Yuniarso; Wening Estiningsih; Saripah (PT. Maju Malaqbi Makkarana, 2026)
This study investigates the relationship between profitability, leverage, and firm size and tax avoidance practices in publicly listed consumer sector firms during the 2020–2024 period. A quantitative approach was applied using panel data regression analysis, with a sample of six companies selected through purposive sampling. Tax avoidance was measured using the Effective Tax Rate (ETR), while profitability, leverage, and firm size were proxied by Return on Assets (ROA), Debt to Equity Ratio (DER), and the natural logarithm of total assets, respectively. Based on model selection procedures, the Random Effect Model (REM) was identified as the most appropriate specification. The results indicate that, both individually and jointly, profitability, leverage, and firm size do not exhibit a statistically significant effect on tax avoidance. Additionally, the coefficient of determination suggests that the model explains only a limited proportion of the variation in tax avoidance behavior. These findings imply that tax avoidance is likely influenced by factors beyond the financial indicators examined, highlighting the need for future research to incorporate broader determinants, including governance and regulatory aspects.